Revisiting the Capital Tax Ambiguity Result - Sheikh Selim (Cardiff University, Cardiff Business School, 2006)
We provide a welfare based interpretation of the capital tax ambiguity result (due to Guo & Lansing, 1999). We show that the sign ambiguity of optimal capital tax rate in an imperfectly competitive economy is mainly due to the welfare cost of investment. The substitution and income effects of profit seeking investment reinforce each other which create a deadweight loss in welfare. Investors cannot perceive this effect and never invest at the right level. This loss is perceived only by the government which motivates capital taxation.
Keywords: D42; E62; H21; H30; 330; Optimal taxation; Monopoly power; Ramsey policy